(untitled) (Research, Society and Development, 2024)
The objective of this research is to study the history of the school supervisor throughout the history of education. Thus, this article makes a bibliographical study on School Management: Administration, Supervision, Guidance and Inspection throughout the history of Education. The article is justified by the need to expand and deepen discussion regarding the topic and permanence in the school environment. This work seeks the trajectory of these professionals throughout the History of Education, which, although guaranteed by law, are still flawed, possibly due to the difficulty of modifying parameters in relation to what is expected from the school. Methodology used, it is a narrative bibliographical research of a qualitative nature. During the research in relation to the readings made in the context of Brazilian Education, the importance of educational management, changes, grows, which represents one of the people who seek to direct the pedagogical work in the school in which quality is achieved throughout the educational process. In studies, the School Manager is a servant specialized in maintaining motivation throughout the history of education through its educational history and transformation.